Cooperative relationships and competitiveness in supermarket sector - Centenaro, Andressa; Laimer, Claudionor Guedes (Review of Business Management, 2017)
Purpose – This article aims to investigate the influence of cooperative relations in the performance of companies in the supermarket sector, comparing the companies associated networks with companies not associated. Design/methodology/approach – The research method employed was a survey research with 31 companies. Findings – The results indicate that the cooperative relationships with suppliers have a positive impact on companies of performance, while the cooperative relationships with competitors and local institutions do not influence the performance. Moreover, it appears that there is no relationship between participation in a network of cooperation and achieving superior performance. However, companies linked to the network present better cooperative relationships with suppliers, which positively impacts the performance and therefore have competitive advantages over companies not associated to networks. Originality/value – The cooperative relationships with suppliers can provide benefits such as reducing logistics costs, improved product portfolio, better negotiating prices and terms, partnership for conducting marketing strategies among others, thus increasing the competitiveness of companies in the supermarket sector.